The RowPerfect ergometer: A training aid for on-water single scull rowing - Elliott, E.; Lyttle, A.; Burkett, O. (Sports Biomechanics, 2002)
The purpose of this study was to compare rowing technique on the dynamic RowPerfect ergometer with a single scull. Eight national-level rowers performed on both the RowPerfect ergometer and in a single scull over 500m, at rates of 24, 26 and 28 strokes/minute. Blade force and oar angle (on-water) and handle force and stroke length (on the ergometer) were measured. Both force and stroke angle/length were normalised from 0 to 100 (where 100 was the peak value.) Body positions of the subjects at both the catch and finish of each of these rowing strokes were also compared for each stroke rate. The coefficient of multiple determination (CMD) was used to measure the consistencey of force curves over a sample of five sequential storkes for each rower. Cross-correlations were performed between the left- and right-side on-water sculling force curves and a mean of these values with the ergometer curve for each rowere. Stroke angle/length, which did not vary with rate, was similar for both forms of rowing. The CMDs showed a high consistency across the normalised strokes of each subject (=0.98). Cross-correlation values of 0.91, 0.92 and 0.93 were recorded between the force curves from the ergometer and on-water trials for stroke rates of 24, 26 and 28 strokes/minute, respectively. The mean trunk, thigh and lower leg angles at the catch and finish of the stroke were also similar across the stroke rates as determined by t-tests. Results indicate that technique used on the RowPerfect ergometer was similar to that for on-water sculling, thus validating its use in off-water training.